Archidiakonat uniejowski w okresie staropolskim - Jabłońska, Anna (Biuletyn Uniejowski, 2012)
This paper addresses selected issues relating to Uniejów archdeaconry in the Old Polish period. The town of Uniejów was the central place – a seat of the archdeaconry, decanate and, most importantly, the collegiate chapter comprising 4 prelacies and 6 canonries, and the requisite number of curacies. The vice-provost was also the village vicar, and the vicearchdeacon was the town vicar. The collegiate church ran a school and fraternities. In the town there also were: church and hospital of Holy Spirit, Oratories of St. Nicolaus, Corpus Christi, St. Adalbert, and St. Anthony the Abbot. The nearby town of Sieradz with its chapter also was one of the main archdeaconry centers. The Uniejów archdeaconry77 was a part of Gniezno archdiocese, and most probably was formed as a result of administrative reforms carried out by archbishop Jakub Świnka. In our times it was devided into four, next five and finally into six decanates comprising between 86 and 106 parishes. The Uniejów chapter was reactivated in 1990.